2019
DOI: 10.1002/ece3.5286
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in spatial distribution: Climate and land use have contrasting effects on the species richness of breeding and wintering birds

Abstract: Aim Many studies have examined large‐scale distributions of various taxa and their drivers, emphasizing the importance of climate, topography, and land use. Most studies have dealt with distributions over a single season or annually without considering seasonality. However, animal distributions and their drivers can differ among seasons because many animals migrate to suitable climates and areas with abundant prey resources. We aim to clarify seasonality in bird distributions and their drivers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…Changes in abiotic and biotic factors force the bird species to ascend and descend avoiding the harsh environmental conditions (Amani et al 2018). Seasonal change affects food, water, and cover availability of bird population, so, they shift/migrate to habitat/areas with surplus resources to maximize breeding success and to minimize high physiological risk and low resource availability (Beuel et al 2016;Girma et al 2017;Kawamura et al 2019), which ultimately brings change in seasonal site-wise richness pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in abiotic and biotic factors force the bird species to ascend and descend avoiding the harsh environmental conditions (Amani et al 2018). Seasonal change affects food, water, and cover availability of bird population, so, they shift/migrate to habitat/areas with surplus resources to maximize breeding success and to minimize high physiological risk and low resource availability (Beuel et al 2016;Girma et al 2017;Kawamura et al 2019), which ultimately brings change in seasonal site-wise richness pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Results of this metaanalysis indicated that the function as habitats compared with natural forests was generally low in cypress family plantations, and the function of plantations for vertebrates increased in autumn-winter. However, the roles of cypress family plantations in each season remain unknown, especially in western Japan, which is an important region for wintering forest birds including migratory species (Kawamura et al 2019). Therefore, to understand the role of plantations as habitats in each season, studies are required on cypress family plantations in western Japan, especially in the wintering season.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Furthermore, for vertebrates, we also examined differences in plantation biodiversity among seasons. This is important because biodiversity in temperate forests is season-dependent (Kawamura et al 2019); in deciduous broad-leaved forests that cover the northern half of Japan, the abundance of food resources for vertebrates drastically change among seasons (Herrera 1978;Huston and Wolverton 2009). Many animal populations consequently alter their range, habitat use, behavior patterns, or food habits (Marchand 2014), suggesting that the habitat function and consequent biodiversity values of plantations may vary with season.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-collinearity among variables was checked using Pearson’s correlation test, and the correlated variables (R 2 ≥ 0.70) were discarded from the analysis [ 49 ]. The number of mammalian species in each camera trap station (site) was taken as a response variable [ 50 ]. The predictor variables used in this analysis includes the elevation, management area (PA/Non-PA), canopy cover, human captures, distance of the camera trap station from nearest road and village (haversine distance) [ 51 ], the proportion of dominant tree species and forest type ( S1 Table ).…”
Section: Discussionmentioning
confidence: 99%